Parent Involvement in Young Adults' Intercollegiate Athletic Careers - Travis E. Dorsch; Katie Lowe; Aryn M. Dotterer; Logan Lyons (University of Kansas Libraries, 2016)
Student-athletes have to balance their sport, academic, and social lives during the transition to college and parent involvement is an integral, but potentially problematic, aspect of this transition. The present study investigated how key parent involvement factors may be associated with positive developmental outcomes in NCAA Division I student-athletes. Student-athlete participants (N = 514) were 46% male, ranged in age from 18 to 25 years (M = 19.76, SD = 1.43), and were recruited from athletic departments at two NCAA Division I member-institutions. Participants completed online surveys with items assessing their perceptions of parent involvement (support from parents, contact with parents, academic engagement, athletic engagement) and student-athlete development (academic self-efficacy, athletic satisfaction, well-being, individuation). After controlling for individual and family demographic factors, parent academic and athletic engagement positively predicted student-athlete academic self-efficacy and athletic satisfaction; parent athletic engagement negatively predicted student-athlete depressive symptoms; all aspects of parent involvement were strong negative predictors of emotional independence; support from parents and parent academic engagement were strong negative predictors of functional independence; and support from parents was a negative predictor and athletic engagement a strong positive predictor of student-athletes' attainment of adult criteria. The present research enhances understanding of the role parent involvement may play in student-athlete development and thus may inform the creation of evidence-based policy and programming at NCAA Division I member-institutions.